Validation of the Portuguese Severe Respiratory Insufficiency Questionnaire for home mechanically ventilated patients - Ribeiro, C (2017)
The aim of this study was to develop and validate the professional translation and cultural adaptation of the Portuguese Severe Respiratory Insufficiency (SRI) Questionnaire. The sample was composed of 93 patients (50 male patients, 53.8%) with a mean age of 66.3 years. The most frequent diagnostic groups were chronic obstructive pulmonary disease, obesity hypoventilation syndrome and restrictive chest wall disorders. The patients were asked to fill in both the SRI and SF-36 questionnaires. Factor analysis of the SRI questionnaire was performed leading to an explained variance of 73%, and resulted in 13 components. When analyzing the reliability, we obtained values for Cronbach's alpha above 0.70 for most subscales with the reliability of the summary scale being even higher (0.84). This professional translation and cultural adaptation of the Portuguese SRI Questionnaire has good psychometric properties which are similar, not only to the original, but also to other translations. These characteristics make this questionnaire applicable to the Portuguese population receiving home mechanical ventilation for severe respiratory insufficiency.